Poly(para-phenylene vinylene) and polynorbornadiene containing rod-coil block copoylmers via combination of acyclic diene metathesis and ring-opening metathesis polymerization - Porz, Michael; Mäker, Dominic; Brödner, Kerstin; Bunz, Uwe H. F. (Macromolecular rapid communications, 2013)
Poly(para-phenylene vinylene) (PPV) and its derivatives are important semiconducting polymers for organic electronics. Herein, an alkene metathesis approach to obtain PPVs is reported. Tri(iso propyl)silyl-substituted norbornadienes are employed as solubilizing agents. As PPV precursors divinylbenzene is used for acyclic diene metathesis and paracyclophane diene for a ring-opening metathesis polymerization-type approach. The resulting polymers are analyzed by gel permeation chromatography (GPC), UV-vis, fluorescence, and nuclear magnetic resonance (NMR) spectroscopy. All of the polymers show good solubility in common solvents.
Gesehen am 06.12.2021